Insights and Challenges of Co-Simulation-based Optimal Pulse Pattern Evaluation for Electric Drives - Hölsch, Lukas; Brosch, Anian; Steckel, Richard; Braun, Tristan; Wendel, Sebastian; Böcker, Joachim; Wallscheid, Oliver (IEEE Transactions on Energy Conversion)
Keywords: Electrical and Electronic Engineering; Energy Engineering and Power Technology

Study on Sample Geometries for Ferrite Characterisation in the MHz-Range - Piepenbrock, Till; Keuck, Lukas; Schachten, Sebastian; Böcker, Joachim; Schafmeister, Frank (PCIM Europe 2024; IEEE International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management)

FEM Modelling of Dimensional-Resonant Inductors for LLC Converters in MHz Range - Piepenbrock, Till; Schafmeister, Frank; Böcker, Joachim (SPEEDAM 2024; 27th International Symposium on Power Electronics, Electrical Drives, Automation and Motion)

Experimentally Verified 22 kW, 30 kHz LLC Resonant Converter Design with new Control for a 1 MW Cascaded H-Bridge Converter - Unruh, Roland; Böcker, Joachim; Schafmeister, Frank (ECCE Europe 2024; IEEE Energy Conversion Congress & Exposition Europe)

Mechatronik und elektrische Antriebe / Mechatronics and electrical drives - Böcker, Joachim

Time-Optimal Model Predictive Control of Permanent Magnet Synchronous Motors Considering Current and Torque Constraints - Brosch, Anian; Wallscheid, Oliver; Böcker, Joachim (IEEE Transactions on Power Electronics)
Keywords: Electrical and Electronic Engineering

Finite Set Sensorless Control With Minimum a Priori Knowledge and Tuning Effort for Interior Permanent Magnet Synchronous Motors - Brosch, Anian; Tinazzi, Fabio; Wallscheid, Oliver; Zigliotto, Mauro; Böcker, Joachim (IEEE Transactions on Power Electronics)
Keywords: Electrical and Electronic Engineering

Pseudo-Labeling Machine Learning Algorithm for Predictive Maintenance of Relays - Winkel, Fabian; Wallscheid, Oliver; Scholz, Peter; Böcker, Joachim (IEEE Open Journal of the Industrial Electronics Society)
Keywords: Electrical and Electronic Engineering; Industrial and Manufacturing Engineering; Control and Systems Engineering

Run-to-Failure Relay Dataset for Predictive Maintenance Research With Machine Learning - Winkel, Fabian; Deuse-Kleinsteuber, Johannes; Böcker, Joachim (IEEE Transactions on Reliability)
Keywords: Electrical and Electronic Engineering; Safety; Risk; Reliability and Quality

An Optimized Third-Harmonic Injection Reduces DC-Link Voltage Ripple in Cascaded H-Bridge Converters up to 50% for all Power Factors - Unruh, Roland; Böcker, Joachim; Schafmeister, Frank (2023 25th European Conference on Power Electronics and Applications (EPE'23 ECCE Europe))
Star-connected cascaded H-bridge Converters require large DC-link capacitors to buffer the second-order harmonic voltage ripple. First, it is analytically proven that the DC-link voltage ripple is proportional to the apparent converter power and does not depend on the power factor for nominal operation with sinusoidal reference arm voltages and currents. A third-harmonic zero-sequence voltage injection with an optimal amplitude and phase angle transforms the 2nd harmonic to a 4th harmonic DC-link voltage ripple. This reduces the voltage ripple by exactly 50% for all power factors at steady-state at balanced conditions. However, this requires 54% additional modules for unity power factor operation and even 100% for pure reactive power operation to account for the increased reference arm voltages due to the large amplitude of the optimal third-harmonic injection. If not enough modules are available, an adaptive discontinuous PWM is utilized to still minimize the voltage ripple for the given number of modules and power factor. With a very limited number of modules (modulation index is 1.15), the proposed method still reduces the DC-link voltage ripple by 24.4% for unity power factor operation. It requires the same number of modules as the commonly utilized 3rd harmonic injection with 1/6 of the grid voltage amplitude and achieves superior results. Simulations of a 10 kV/1 MVA system confirm the analysis.
Keywords: Cascaded H-Bridge; Solid-State Transformer; Capacitor voltage ripple; Zero sequence voltage; Third harmonic injection

Fade-Over Strategy for use of Model Predictive Direct Self-Control with Field-Oriented Control - Pena, Mario; Meyer, Michael; Wallscheid, Oliver; Böcker, Joachim (2023 IEEE International Electric Machines and Drives Conference (IEMDC))

Model Predictive Direct Self-Control for Six-Step Operation of Permanent-Magnet Synchronous Machines - Pena, Mario; Meyer, Michael; Wallscheid, Oliver; Böcker, Joachim (IEEE Transactions on Power Electronics)
Keywords: Electrical and Electronic Engineering

Online system identification and excitation for thermal monitoring of electric machines using machine learning and model predictive control - Gedlu, Emebet Gebeyehu; Wallscheid, Oliver; Böcker, Joachim; Nelles, Oliver (2023 IEEE 14th International Symposium on Diagnostics for Electrical Machines, Power Electronics and Drives (SDEMPED))

Reducing Contact Bouncing of a Relay by Optimizing the Switch Signal During Run-Time - Winkel, Fabian; Scholz, Peter; Wallscheid, Oliver; Böcker, Joachim (IEEE Transactions on Automation Science and Engineering)
Keywords: Electrical and Electronic Engineering; Control and Systems Engineering

Advanced Synchronous Rectification for an IGBT-Based ZCS LLC Converter with High Output Currents for a 2 kW Automotive DC-DC Stage - Urbaneck, Daniel; Böcker, Joachim; Schafmeister, Frank (PCIM Europe 2023; IEEE International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management)

An Open-Source Transistor Database and Toolbox as an Unified Software Engineering Tool for Managing and Evaluating Power Transistors - Förster, Nikolas; Rehlaender, Philipp; Wallscheid, Oliver; Schafmeister, Frank; Böcker, Joachim (Proc. 37th IEEE Applied Power Electronics Conference (APEC))

Robust Hysteresis Control for LLC Resonant Converters Using a Fully Isolated Measurement Scheme - Keuck, Lukas; Schafmeister, Frank; Böcker, Joachim (Proc. IEEE International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management (PCIM))

Model Predictive Torque Control for Permanent Magnet Synchronous Motors Using a Stator-Fixed Harmonic Flux Reference Generator in the Entire Modulation Range - Brosch, Anian; Wallscheid, Oliver; Böcker, Joachim (IEEE Transactions on Power Electronics)
Keywords: Electrical and Electronic Engineering

Concept Study of an LLC Converter with Magnetically Resonant Inductor - Böcker, Joachim (2022 International Symposium on Power Electronics, Electrical Drives, Automation and Motion (SPEEDAM))

Long-Term Memory Recursive Least Squares Online Identification of Highly Utilized Permanent Magnet Synchronous Motors for Finite-Control-Set Model Predictive Control - Brosch, Anian; Wallscheid, Oliver; Böcker, Joachim (IEEE Transactions on Power Electronics)
Keywords: Electrical and Electronic Engineering

Experimental Comparison of FPGA-Implemented Model Predictive Voltage Control to Cascaded Proportional Resonant Control for a Three-Phase Four-Wire Three-Level Grid-Forming Inverter of 250 kVA - Lange, Jarren; Schmies, Dominik; Stille, Karl Stephan Christian; Böcker, Joachim; Wallscheid, Oliver (EPE'22 ECCE Europe)

Adaptive Operating Strategy for Induction Motors Under Changing Electrical-Thermal Conditions - Stender, Marius; Becker, Marius; Wallscheid, Oliver; Böcker, Joachim (48th Annual Conference of the Industrial Electronics Society (IECON))

An Open-Source Transistor Database and Toolbox as a Unified Software Engineering Tool for Managing and Evaluating Power Transistors - Förster, Nikolas; Rehlaender, Philipp; Wallscheid, Oliver; Schafmeister, Frank; Böcker, Joachim (2022 IEEE Applied Power Electronics Conference and Exposition (APEC))

An Open-Source FEM Magnetics Toolbox for Power Electronic Magnetic Components - Förster, Nikolas; Piepenbrock, Till; Rehlaender, Philipp; Wallscheid, Oliver; Schafmeister, Frank; Böcker, Joachim (PCIM Europe 2022; International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management)

Thermal neural networks: Lumped-parameter thermal modeling with state-space machine learning - Kirchgässner, Wilhelm; Wallscheid, Oliver; Böcker, Joachim (Engineering Applications of Artificial Intelligence)

Learning Thermal Properties and Temperature Models of Electric Motors with Neural Ordinary Differential Equations - Kirchgässner, Wilhelm; Wallscheid, Oliver; Böcker, Joachim (2022 International Power Electronics Conference (IPEC-Himeji 2022- ECCE Asia))

LLC Resonant Converter Modulations for Reduced Junction Temperatures in Half-Bridge Mode and Transformer Flux in the On-the-Fly Morphing Thereto - Rehlaender, Philipp; Wallscheid, Oliver; Schafmeister, Frank; Böcker, Joachim (IEEE Transactions on Power Electronics)
Keywords: Electrical and Electronic Engineering

Application of Thermal Neural Networks on a Small-Scale Electric Motor - Kirchgässner, Wilhelm; Wöckinger, Daniel; Wallscheid, Oliver; Bramerdorfer, Gerd; Böcker, Joachim (IKMT 2022; 13. GMM/ETG-Symposium)

Experimental Demonstration of a 2.2kW Active-Clamp Converter for High-Current Wide-Voltage-Transfer Ratio Applications - Rehlaender, Philipp; Korthauer, Bastian; Schafmeister, Frank; Böcker, Joachim (2022 24th European Conference on Power Electronics and Applications (EPE’22 ECCE Europe))

Phase-Shift Modulation for Flying-Capacitor DC-DC Converters - Rehlaender, Philipp; Schafmeister, Frank; Böcker, Joachim (2022 24th European Conference on Power Electronics and Applications (EPE’22 ECCE Europe))

Data-Driven Adaptive Torque Oscillation Compensation for Multi-Motor Drive Systems - Brosch, Anian; Rauhaus, Johann; Wallscheid, Oliver; Böcker, Joachim; Zimmer, Detmar (IEEE Open Journal of Industry Applications)

Zero-Sequence Voltage Reduces DC-Link Capacitor Demand in Cascaded H-Bridge Converters for Large-Scale Electrolyzers by 40% - Unruh, Roland; Schafmeister, Frank; Böcker, Joachim (24th European Conference on Power Electronics and Applications (EPE'22 ECCE Europe))
Cascaded H-bridge Converters (CHBs) are a promising solution in converting power from a three-phase medium voltage of 6.6 kV...30 kV to a lower DC-voltage in the range of 100 V...1 kV to provide pure DC power to applications such as electrolyzers for hydrogen generation, data centers with a DC power distribution and DC microgrids. CHBs can be interpreted as modular multilevel converters with an isolated DC-DC output stage per module, require a large DC-link capacitor for each module to handle the second harmonic voltage ripple caused by the fluctuating input power within a fundamental grid period. Without a zero-sequence voltage injection, star-connected CHBs are operated with approximately sinusoidal arm voltages and currents. The floating star point potential enables to utilize different zero-sequence voltage injection techniques such as a third-harmonic injection with 1/6 of the grid voltage amplitude or a Min-Max voltage injection. Both well-known methods have the advantage to reduce the peak arm voltage and thereby the number of required modules by 13.4 % (to √ 3 2). This paper proves analytically that the third-harmonic injection with 1/6 of the grid voltage amplitude reduces the second harmonic voltage ripple by only 15.1 % compared to no-voltage injection for unity power factor operation and balanced grid voltages. Then it is shown, that the Min-Max injection has the often overlooked advantage of reducing the second harmonic voltage ripple by even 18.8 %. By applying the here proposed zero-sequence voltage injection in saturation modulation, the second harmonic voltage ripple of the DC-link capacitors is reduced by even 24.3 %, while still requiring the same number of modules as the Min-Max injection. For a realistic number of reserve modules, the overall energy ripple in the DC-link capacitors is reduced by 40 %.
Keywords: Cascaded H-Bridge; Solid-State Transformer; Zero sequence voltage; Third harmonic injection; Capacitor voltage ripple

An Open-Source FEM Magnetic Toolbox for Calculating Electric and Thermal Behavior of Power Electronic Magnetic Components - Förster, Nikolas; Hölscher, Jonas; Piepenbrock, Till; Rehlaender, Philipp; Wallscheid, Oliver; Schafmeister, Frank; Böcker, Joachim (2022 24th European Conference on Power Electronics and Applications (EPE’22 ECCE Europe))

Elektrische Antriebe – Regelung von Antriebssystemen - Schröder, Dierk; Böcker, Joachim

Common-Mode-Free Bidirectional Three-Phase PFC-Rectifier for Non-Isolated EV Charger - Strothmann, Benjamin; Schafmeister, Frank; Böcker, Joachim (2021 IEEE Applied Power Electronics Conference and Exposition (APEC))
DC-DC converters for on-board chargers (OBC) of electrical vehicles are usually galvanically isolated allowing modular single-phase PFC front-end solutions, but require transformers which are more bulky, costly and lossy than inductors of non-isolated DC-DCs. Furthermore, for vehicle-to-grid applications, bidirectional converters with transformers are generally more complex and have a higher count on semiconductor switches than transformerless solutions. However, when using non-isolated DC-DC converters within an OBC, the large common-mode (CM) capacitance comprising capacitive parasitics of the traction battery as well as explicit Y-capacitors connecting the high-voltage DC-system (HV-system) within specific HV-loads to ground has to be considered. For the PFC front-end stage, when supplied from the three-phase mains this means that generation of high-frequency and high-amplitude CM voltages, as it is common e.g. with the conventional six-switch full-bridge converter, has to be strictly avoided. For this reason, a modified topology is suggested leading to a different mode of operation and to a very low common-mode noise behaviour: The three-phase four-wire full-bridge PFC with split DC-link, whose midpoint is connected to the mains neutral provides very stable potentials at the DC-link rails and therefore it can be classified as Zero-CM-topology.For dedicated single-phase operation, as required for most OBC, an additional balancing leg may be added to the topology to reduce the required DC-link capacitance and allow non-electrolytic capacitors.The function of the bidirectional Zero-CM three-phase four-wire full-bridge PFC was verified by simulation and on an 11 kW-laboratory sample. The power factor is above 0.999 and an efficiency of 98 % is measured.
Keywords: Three-phase four-wire; OBC; Y2G; PFC; CM; EY charger; balancing circuit

Model Predictive Control of Permanent Magnet Synchronous Motors in the Overmodulation Region Including Six-Step Operation - Brosch, Anian; Wallscheid, Oliver; Böcker, Joachim (IEEE Open Journal of Industry Applications)

Temperature estimation of electric machines using a hybrid model of feed-forward neural and low-order lumped-parameter thermal networks - Gedlu, Emebet Gebeyehu; Wallscheid, Oliver; Böcker, Joachim (2021 IEEE International Electric Machines & Drives Conference (IEMDC))

Interleaved Single-Stage LLC Converter Design Utilizing Half- and Full-Bridge Configurations for Wide Voltage Transfer Ratio Applications - Rehlaender, Philipp; Schafmeister, Frank; Böcker, Joachim (IEEE Transactions on Power Electronics)
Keywords: Electrical and Electronic Engineering

Design and Analysis of a Regenerative Snubber for a 2.2 kW Active-Clamp Forward Converter with Low-Voltage Output - Korthauer, Bastian; Rehlaender, Philipp; Schafmeister, Frank; Böcker, Joachim (2021 IEEE Applied Power Electronics Conference and Exposition (APEC))

Single-Phase Operation of Common-Mode-Free Bidirectional Three-Phase PFC-Rectifier for Non-Isolated EV Charger with Minimized DC-Link - Strothmann, Benjamin; Book, Gerrit; Schafmeister, Frank; Böcker, Joachim (PCIM Europe digital days 2021; International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management)
In electric vehicles (EV) the large common-mode (CM) capacitance comprising capacitive parasitics of the traction battery as well as explicit Y-capacitors connecting within specific loads the high-voltage DC-system (HV-system) to ground, can cause issues when using non-isolated EV Chargers. One solution for a power factor correction (PFC) rectifier that is capable to operate with a non-isolated DC-DC converter, is the three-phase four-wire full-bridge PFC, with split DC-link, whose midpoint is connected to the mains neutral. Therefore, it provides very stable potentials at the DC-link rails and accordingly can be classified as Zero-CM topology, which facilitates a common-mode-free operation. When to be operated at a single-phase supply, which is a common requirement for On-board chargers (OBCs) this topology results in the voltage-doubler PFC (V2-PFC) being characterised by a comparably large DC-link voltage ripple at mains frequency. If the DC-link capacitance shall be minimized, for instance to avoid lifetime-limited electrolytic capacitors, two more circuits in addition to the original V2-PFC are proposed for keeping the common-mode-free operation: A balancing circuit (BC), that balances the voltages over the split capacitors and a ripple port (RP), that buffers the 100 Hz power pulsation of the mains. For both circuits the available two bridge legs of the three-phase topology in single-phase operation may be utilized. A 3.7 kW laboratory sample verifies the functionality of the additional circuits in conjunction with the V2-PFC and achieves an efficiency of 95 %.

LLC Converter in Capacitive Operation Utilizing ZCS for IGBTs – Theory, Concept and Verification of a 2 kW DC-DC Converter for EVs - Urbaneck, Daniel; Rehlaender, Philipp; Böcker, Joachim; Schafmeister, Frank (2021 IEEE Applied Power Electronics Conference and Exposition (APEC))
LLC resonant converters typically employ power MOSFETs in their inverter stage. The generally weak reverse recovery behaviour of the intrinsic body diodes of those MOSFETs causes significant turn-on losses when being forced to hard commutations. Continuous operation in this way will lead to self-destruction of the transistors. Consequently, zero-voltage switching (ZVS) is essential in a MOSFET-based inverter stage. To ensure ZVS, the LLC converter is operated in the inductive region. On the contrary, IGBTs show dominant turn-off losses and are therefore conventionally not applied in LLC converters typically requiring high switching frequencies to achieve low output voltages. However, if the LLC converter is intentionally designed for capacitive operation, zero-current switching (ZCS) is enabled and thus robust and cost-efficient IGBTs can be applied in the inverter stage. The aim of this work is to investigate the use IGBTs in the inverter of an LLC converter. The theory behind the capacitive operated LLC is derived using a switched simulation model and compared with the fundamental harmonic approximation (FHA). The results prove FHA to be useless for practical converter design. Instead, a stress value analysis based on switched model simulations is proposed to the design a capacitive operated LLC utilizing ZCS. A 2 kW prototype for on-board EV applications was built to verify the theory and design approach. The prototype confirms the derived theory and thus the deployment of IGBTs in the inverter stage of LLC resonant converters. Synchronous rectification turns out to require a specific control solution, but if given the resulting efficiency in the most critical operation point exceeds the value of a MOSFET-based (inductive operated) LLC-design of an identical application. Therefore, this concept should be further developed.

Accurate Torque Control for Induction Motors by Utilizing a Globally Optimized Flux Observer - Stender, Marius; Wallscheid, Oliver; Böcker, Joachim (IEEE Transactions on Power Electronics)
Keywords: Electrical and Electronic Engineering

Accurate Torque Estimation for Induction Motors by Utilizing a Hybrid Machine Learning Approach - Stender, Marius; Wallscheid, Oliver; Böcker, Joachim (2021 IEEE 19th International Power Electronics and Motion Control Conference (PEMC))

Combined Electrical-Thermal Gray-Box Model and Parameter Identification of an Induction Motor - Stender, Marius; Wallscheid, Oliver; Böcker, Joachim (IECON 2021 – 47th Annual Conference of the IEEE Industrial Electronics Society)

Gray-Box Loss Model for Induction Motor Drives - Stender, Marius; Wallscheid, Oliver; Böcker, Joachim (2021 IEEE 19th International Power Electronics and Motion Control Conference (PEMC))

Comparison of Artificial Neural Network and Least Squares Prediction Models for Finite-Control-Set Model Predictive Control of a Permanent Magnet Synchronous Motor - Hanke, Sören; Wallscheid, Oliver; Böcker, Joachim

Data-Driven Permanent Magnet Temperature Estimation in Synchronous Motors with Supervised Machine Learning: A Benchmark - Kirchgässner, Wilhelm; Wallscheid, Oliver; Böcker, Joachim (IEEE Transactions on Energy Conversion)

Torque and Inductances Estimation for Finite Model Predictive Control of Highly Utilized Permanent Magnet Synchronous Motors - Brosch, Anian; Wallscheid, Oliver; Böcker, Joachim (IEEE Transactions on Industrial Informatics)

Comparison of unidirectional Three- and Four-Wire based Boost PFC-Rectifier Topologies for Non-Isolated Three-Phase EV On-Board Chargers under Common-Mode Aspects - Hagemeyer, Marc; Wallmeier, Peter; Schafmeister, Frank; Böcker, Joachim (Proc. 36th IEEE Applied Power Electronics Conference (APEC))

Adaptive Zero-Sequence Voltage Injection for Modular Solid-State Transformer to Compensate for Asymmetrical Fault Conditions - Unruh, Roland; Lange, Jarren; Schafmeister, Frank; Böcker, Joachim (23rd European Conference on Power Electronics and Applications (EPE'21 ECCE Europe))
Modular solid-state transformers (SSTs) are a promising technology in converting power from a 10kV three-phase medium voltage to a lower DC-voltage in the range of 100…400V to provide pure DC power to applications such as electrolyzers for hydrogen generation, data centers with a DC power distribution and DC micro grids. Modular SSTs which can be interpreted as modular multilevel converters with an isolated DC-DC output stage per module, are designed with redundant modules to increase reliability. Usually, each of the three arms operates independently, and therefore, only a fixed number of faulty modules can be compensated in each arm, even if all modules are operational in the remaining two arms. With the proposed zero-sequence voltage injection, up to 100% more faulty modules can be compensated in an arm by employing the same hardware. In addition, module power imbalances are nearly eliminated by utilizing a fundamental frequency zero-sequence voltage. A dominant 3rd harmonic zero-sequence voltage injection in combination with the 5th, 7th and several higher order harmonics with adaptive (small) amplitudes minimize the required arm voltages at steady-state. For nominal operation or symmetrical faults, the proposed technique is equivalent to the well known Min-Max voltage injection, which already reduces the peak arm voltage by 13.4% compared to a constant star point potential. A statistical analysis proves, that the expected number of tolerable faulty modules of the 1MW SST increases by 12% without the need for additional hardware.
Keywords: Solid-State Transformer; Zero sequence voltage; Fault handling strategy; Power balance control technique; Three-phase system